Bioremediation of heavy metal polluted water using immobilized freshwater green microalga, botryococcus sp. - Joan Iye, Onalo (2015)
Heavy metal containing wastewater are regarded as highly toxic to the aquatic environment and to life in general due to their bio-accumulating, cytotoxic, mutagenic and carcinogenic effects on life. Bioremediation is the use of biological materials (e.g. microalgae) in the removal of toxic compounds from the environment such as the heavy metals which is considered more cost effective and environmentally friendly when compared to the physical and chemical methods. The present study was undertaken to check for the heavy metal bioremoval efficiency of free and immobilized Botryococcus sp. Four heavy metals were studied and the free cells efficiently reduced Chromium which is equivalent to 94%, followed by Copper (45%), Arsenic (9%) and Cadmium (2%). For the immobilized biomass, the highest (P<0.05) removal efficiency was recorded in the highest biomass concentration (i.e. 15 beads/ml) for Cadmium, Arsenic and Chromium at 76%, 68% and 67%. Whereas, the highest (P<0.05) removal of copper was observed in the blank alginate beads at 84%. The positive control (free cells) recorded the highest (P<0.05) reduction for biological oxygen demand (BOD) whereas, the 15 beads/ml gave the highest (P<0.05) reduction for control gave the highest (P<0.05) reduction for the Chemical oxygen demand (COD). In the LD50 experiment, immobilized biomass harvested from the bioremoval study experiment were used on fishes for toxicity testing. A total of 100% mortality was recorded in the positive control after 24 hours whereas, 3% mortality was observed in negative control and in the 10 beads/ml treatment after 72 hours. No mortality was found in any other treatment after a period of 96 hours. The results obtained from this study suggests that, immobilized cells of Botryococcus sp. is efficient in the bioremoval of heavy metals from contaminated waters and also have great potential in the biotransformation of toxic compounds to less-toxic forms.